Perspective Taking Ability in Psychologically Maltreated Children: A Protective Factor in Peer Social Adjustment - Cigala, Ada; Mori, Arianna (Frontiers in Psychology, 2022)
Perspective taking is conceptualized as a multidimensional construct characterized by three components: cognitive, affective, and visual. The experience of psychological maltreatment impairs the child’s emotional competence; in particular, maltreated children present difficulty in understanding and regulating emotions and in social understanding ability. In addition, the literature contains several contributions that highlight maladaptive behaviors of children with a history of maltreatment in peer interactions in the school context. Perspective taking ability has rarely been studied in maltreated children and the existing studies have produced different and often conflicting results that require further insights. On the grounds of these premises, the main objective of the present research is to investigate perspective taking ability in preschool children from maltreating and non-maltreating family contexts and its role in social adjustment, in terms of prosocial and aggressive behavior toward peers inside the kindergarten. A second objective is to verify the effectiveness of a training aimed to promote perspective taking ability in victims of psychological maltreatment. This research, organized into two separate studies, involved 249 preschool children: 206 children from non-maltreating family contexts and 43 brought up in psychologically maltreating families. Perspective taking was measured via the administration of several tests, and prosocial behavior and aggressiveness were observed via non-participant observations in the school context. The training involved maltreated children in small-group meetings based on familiar and appealing activities within the mother–child community. The overall results show that children’s perspective taking ability, in particular the affective perspective taking, contributed to social adjustment. In fact, greater affective perspective taking ability was correlated to a higher frequency of prosocial behaviors toward peers and minor frequency of aggressiveness. Finally, the results of the training (pre/post-test comparison) showed an increase in perspective taking, especially in the affective dimension, and a consequent increase in prosocial behaviors and a decrease in aggressive ones. Therefore, the affective perspective taking ability seems to represent a very significant protective factor, which should be focused and strengthened in order to improve the social adaptation of preschool children who are victims of psychological abuse.